Community resilience: A meta-study of international development rhetoric in emerging economies. Issue 2 (15th March 2019) - Haggard, Rachel; Cafer, Anne; Green, John
ABSTRACT: Understood generally, community resilience (CR) is the ability of communities to adapt, absorb, mitigate, and recover from shocks and stressors in such a way that facilitates positive future outcomes and reduces overall vulnerability to future shocks and stressors. The core of this definition relates to sustainability and the capability of socio-ecological systems and communities to adapt and transform to both day-to-day fluctuations and stressors as well as major disasters. This meta-study seeks to shed light on whether and how studies claiming to use a CR framework address and measure the four outcomes that result when a community is resilient. This analysis uses USAID's resilience framework to assess whether the international development literature studies the outcomes of CR: touching upon nutrition, food security, economic security, and ecological sustainability.